SOSIALISASI BAHAYA STUNTING DI KOTA PALU - Ardi Munir, Muhammad; Fitriana, Yuli; Aryuni , Muthia (Jurusan Farmasi FMIPA Universitas Tadulako, 2022)
Stunting is one of the nutritional problems currently being faced by Indonesia, especially in the area of Central Sulawesi Province. Based on research in the field, there are several problems. The identification of the problem in this study is that children are the successors of assets in the future, Indonesia, the second country with the highest incidence of stunting in the Southeast Asia region, the incidence of stunting in Central Sulawesi is still above the national average and the lack of awareness of parents, especially mothers in the dangers of stunting. for child development. Efforts are being made to overcome the stunting problem, namely by maintaining the child's diet, parenting by parents as well as sanitation and clean water. The diet in question in this case is a good and sufficient intake of energy and protein in children. Efforts made by the local government are providing additional food and vitamin A for toddlers and food supplements and blood boosters for pregnant women as a way to prevent stunting or stunting due to malnutrition. The pattern of parenting in this case, namely the knowledge of parents about stunting is very lacking. Mothers do not understand the various kinds of intake that must be met for their children. In addition to malnutrition, lack of access to clean water and poor sanitation is also a cause of stunting. On the other hand, a healthy lifestyle in the use of clean water that is applied by the community is very less noticed. This community service activity aims to provide socialization of the dangers of stunting in children. This socialization was attended by about 30 with the speaker dr. Yuli Fitriana, M.K.M. In addition to stunting socialization, the speaker also gave some tips in dealing with child stunting.